Should We Stay or Should We Go? Firms' Decision on Services Mode of Supply - Holger Breinlich; Martina Magli (CESifo GmbH, 2024)
Services account for one-third of global trade, yet little is known about the impact of trade restrictions on services trade. To make progress in this area, it is crucial to understand through which Modes services are traded (cross-border, movement of people, foreign investment or consumption abroad) and how firms substitute among these Modes. We provide novel micro-level evidence on firms' mode choices, combining detailed data on UK firms' trade and affiliates' sales. We also estimate the substitution between trade Modes using Brexit as an exogenous shock, finding that UK firms increasingly relied on local affiliate sales to serve the EU market after 2016. This shift protected firm-level services exports from expected higher trade barriers after Brexit, but at the cost of lower domestic employment.
Keywords: F13; F14; F16; 330; trade shocks; services trade; modes of supply; Brexit